the effect of using stabile and variable exercise in learning on some basic skills ( open and close ) in football - Abedulhussein, Mohammed (Journal of Physical Education, 2007)
The first chapter contains the introduction and the importance of the study and also the the reason that why we chose this study and the display of the problem of the research and the aims and the hypothesis and the fields of the study The chapter tow contains the theoretical studies the relevant with research which we detail the importance and definition of learning and the methods of learning ( stabile and variable ) and the skills in football The third chapter contains the method of the research which recognize the method of the research that the researcher use also the sample of the research also pilot study and equilivant and homogeneity and statistical methods that we used in this research The fourth chapter contains the display of results that we obtain and discus thru statistical methods Finally the fifth chapter consist of the conclusion that the researcher gains and also contains the recommendation which resolve the problem of the research